A wareness of recycling construction waste material in construction industry / Nazatul Ilani Mohamed Nazri - Mohamed Nazri, Nazatul Ilani (2014)
Waste is produced in everyday life. Waste is generated from all substances that would be used. As we know the waste were getting increased day by day and required more landfill for disposal. Certain source of waste came from construction material. In Malaysia, construction site tend to dispose the waste than handle by appropriate way. The way of recycling waste should be practiced by all parties involved in construction industry. This can be confirmed by conduct a structured interview within the checklist and questionnaire regarding status and awareness of construction waste management and recycling method handling procedure construction waste material. Thus, the result will be obtained based on five selected construction site around Klang Valley.